2017
DOI: 10.1111/jdv.14681
|View full text |Cite
|
Sign up to set email alerts
|

Biological false‐positive venereal disease research laboratory test in cerebrospinal fluid in the diagnosis of neurosyphilis – a case‐control study

Abstract: Biological false-positive VDRL-CSF is common in a setting where patients are tested without first establishing a serological diagnosis of syphilis. Serological testing should be performed prior to CSF evaluation for neurosyphilis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…During the entire study period, not a single positive CSF-VDRL obtained in the absence of positive blood syphilis testing led to a diagnosis of neurosyphilis, highlighting the importance of considering pre-test probability prior to ordering CSF-VDRL, particularly in low-prevalence settings. This false-positivity rate is consistent with a recent study by Zheng et al, which reported a false-positive rate of 25 However, the cause of the false-positive results differed. In our study, a large percentage of patients with false-positive CSF-VDRL results were ultimately diagnosed with neoplastic meningitis, mostly meningeal carcinomatosis associated with primary lung cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…During the entire study period, not a single positive CSF-VDRL obtained in the absence of positive blood syphilis testing led to a diagnosis of neurosyphilis, highlighting the importance of considering pre-test probability prior to ordering CSF-VDRL, particularly in low-prevalence settings. This false-positivity rate is consistent with a recent study by Zheng et al, which reported a false-positive rate of 25 However, the cause of the false-positive results differed. In our study, a large percentage of patients with false-positive CSF-VDRL results were ultimately diagnosed with neoplastic meningitis, mostly meningeal carcinomatosis associated with primary lung cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Zheng et al did not find any cases of neoplastic meningitis. 25 The difference between our findings is likely due in part to different populations and/or practice patterns. The Zheng study was conducted in Singapore, and importantly, their study was conducted over a 3-year period, whereas we analyzed data spanning 24 years.…”
Section: Discussionmentioning
confidence: 58%
“…Antilipoidal antibodies are produced not only as a consequence of syphilis and other treponemal diseases but also in response to non-treponemal diseases of an acute and chronic nature in which tissue damage occurs ( 10 ). Although the incidence of biological false-positive VDRL tests is rare in spinal fluid samples ( 11 ), some studies have reported false-positive CSF VDRL results in the setting of central nervous system malignancy or HIV infection ( 12 14 ). However, for these syphilis patients, negative CSF-VDRL-10 results but positive CSF-VDRL-17 results may be indications for a very early phase of asymptomatic neurosyphilis and contribute to early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…6 CSF VDRL has a high specificity barring blood contamination 6 and a positive predictive value of 100% with a positive serum nontreponemal test. 7 The diagnosis of Lyme disease, however, is not straightforward, and we suggest following a diagnostic algorithm (Figure 2). His initial serum Lyme WB had only 1 positive IgG band (41 kD), with negative IgM.…”
Section: Sectionmentioning
confidence: 99%